Flow cytometry-based rapid detection of Staphylococcus aureus and Pseudomonas aeruginosa using fluorescent antibodies. Issue 53 (2nd December 2022) - Kim, Joo-Kyung; Yun, Hanool; Yeom, Chang-Hun; Kim, Eun-Jung; Kim, Wooseong; Lee, Chang-Soo; Kim, Byung-Gee; Jeong, Hee-Jin
Abstract : Flow cytometry-based rapid and convenient pathogen detection. Abstract : Staphylococcus aureus ( S. aureus ) and Pseudomonas aeruginosa ( P. aeruginosa ) are major pathogens frequently detected in food and beverage poisoning, and persistent infections. Therefore, the development of a rapid method that can detect these pathogens before serious multiplication is required. In this study, we established a flow cytometry (FCM)-based detection method that allows rapid acquisition of cell populations in fluid samples by using a fluorescent antibody against S. aureus or P. aeruginosa . Using this method, we detected these pathogens with a 10 3 to 10 5 CFU order of limit of detection value within 1 hour. The FCM-based method for the detection of S. aureus and P. aeruginosa offers the possibility of high-throughput analysis of pathogens in food, environmental, and clinical sources.